2012
DOI: 10.1186/1756-8722-5-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent updates on the role of microRNAs in prostate cancer

Abstract: MicroRNAs (miRNAs) are short non-coding RNAs that are involved in several important biological processes through regulation of genes post-transcriptionally. Carcinogenesis is one of the key biological processes where miRNAs play important role in the regulation of genes. The miRNAs elicit their effects by binding to the 3' untranslated region (3'UTR) of their target mRNAs, leading to the inhibition of translation or the degradation of the mRNA, depending on the degree of complementary base pairing. To-date mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 86 publications
(155 reference statements)
2
44
0
2
Order By: Relevance
“…8 miRNAs play a crucial role in the regulation of almost every biological process, including differentiation, apoptosis, cell cycle, development and metabolism. 9,10 Moreover, dysregulation of any of these processes due to abnormal expression of miRNAs or alterations in their machinery of biogenesis has been implicated in cancer, including PCa. 11,12 Although miRNAs have been proposed to function as either oncogenes or tumor-suppressor genes, 13 most human tumors are characterized by a general defect in miRNA production that results in global downregulation of miRNA expression.…”
Section: Enoxacin Inhibits Growth Of Prostate Cancer Cells and Effectmentioning
confidence: 99%
“…8 miRNAs play a crucial role in the regulation of almost every biological process, including differentiation, apoptosis, cell cycle, development and metabolism. 9,10 Moreover, dysregulation of any of these processes due to abnormal expression of miRNAs or alterations in their machinery of biogenesis has been implicated in cancer, including PCa. 11,12 Although miRNAs have been proposed to function as either oncogenes or tumor-suppressor genes, 13 most human tumors are characterized by a general defect in miRNA production that results in global downregulation of miRNA expression.…”
Section: Enoxacin Inhibits Growth Of Prostate Cancer Cells and Effectmentioning
confidence: 99%
“…Numerous studies have demonstrated that microRNAs (miRNAs/miRs) negatively regulate the expression of a number of genes that are important for tumorigenesis and development, which highlights a novel mechanism underlying PCa pathogenesis (7)(8)(9)(10)(11)(12). miRNAs are endogenously expressed small, non-coding, single-stranded RNAs.…”
Section: Introductionmentioning
confidence: 99%
“…This can occur via a perfect complimentary binding of the miRNA to the target mRNA (endonucleolytic cleavage of the mRNA) or by an imperfect complimentary binding to the target mRNA (translation repression). 32 Due to their cell cycle interference, miRNAs are involved either as oncogenes or as oncosuppressors in the pathogenesis of a huge variety of human cancers such as lung cancer, 33,34 prostate cancer, 35 colorectal cancer, 36,37 leukemia, [38][39][40] gliomas 41 and medulloblastoma, 42 diffuse large B-cell lymphoma, 43 hepatocellular carcinoma (HCC), 44 gastric cancer, 45,46 osteosarcoma, 47 renal cell carcinoma, 48 BC, 49 and OC. 50 Particularly, their presence in the blood has been shown to be associated with histology, clinical stage, survival, and oncogenic expression in OC and BC.…”
Section: Introductionmentioning
confidence: 99%